Aromatic hydroxylation and sulfation of 5-hydroxyflavone by Streptomyces fulvissimus. - Ibrahim, A R (1989)
The conversion of 5-hydroxyflavone by various microorganisms was studied. Among them, Streptomyces fulvissimus was the sole microbe which produced a new polar metabolite from 5-hydroxyflavone in addition to 5,4-dihydoxy- and 5,3,4-trihydroxyflavone. The structure of this polar metabolite was determined to be 5,4-dihydroxyflavone-4-sulfate on the basis of mass, infrared, and nuclear magnetic resonance spectroscopies. These results demonstrate that S. fulvissimus catalyzes sulfation at the 4 position of 4,5-dihydroxyflavone.